Mammary tissue proteomics in a pig model indicates that dietary valine supplementation increases milk fat content via increased de novo synthesis of fatty acid. Issue 11 (16th September 2021) - Che, Long; Xu, Mengmeng; Gao, Kaiguo; Wang, Li; Yang, Xuefen; Wen, Xiaolu; Xiao, Hao; Li, Mengyun; Jiang, Zongyong
Abstract: Milk fat is a major source of energy that determines the growth of neonates. Recently, studies have shown that valine is closely related to lipid metabolism. Therefore, this study was designed to investigate the effects of dietary valine supplementation on milk fat synthesis using a pig model. Thirty gilts were allotted to low (LV, total valine:lysine = 0.63:1), medium (MV, total valine:lysine = 0.73:1), and high (HV, total valine:lysine = 0.93:1) valine feeding levels from Day 75 of gestation till farrowing. The results demonstrated that the concentration of milk fat at Days 1, 3, and 7 of lactation in the HV group was higher than that in the MV and LV groups. The HV group had an increased (p < .05) proportion of total saturated and monounsaturated fatty acids than the other groups. Examination of mammary tissue proteomics in the HV and LV groups revealed 121 differentially expressed proteins (68 upregulated and 53 downregulated in the HV group). The upregulated proteins in the HV group were relevant to some crucial pathways related to milk fat synthesis, including fatty acid biosynthesis and metabolism, the AMPK signaling pathway, and oxidative phosphorylation. Furthermore, the key proteins involved in fatty acid synthesis (ACACA and FASN) were identified, and their expression levels were verified (p < .05) using Western blotting. Our findings revealed that dietary valine supplementation improves milk fat synthesis by modulating the expression of fatty acid synthesis–related proteins in mammary tissues. Abstract : Dietary valine supplementation increases the content of milk fat in the colostrum Dietary valine supplementation increases the proportion of fatty acids in colostrum. Valine can activate the signaling pathway related to fatty acids synthesis. Valine promote fatty acids synthesis may via the upregulation of proteins ACACA and FASN